PERTUMBUHAN TANAMAN KETAPANG (Terminalia catappa L) DENGAN PENAMBAHAN PUPUK ORGANIK DAN NPK PADA TAILING DI PERSEMAIAN - Musrini, Eka; Muin, Abdurrani; Burhanuddin, Burhanuddin (Universitas Tanjungpura, 2020)
Restoration and revegetation must be done to recover the post-mining land ecosystem. The strategy of one vegetative that could be applied to rehabilitate degraded the post-mining land is revegetation with the applications the organic and NPK fertilizer to improve the land conditions and choose the suitable of the plant. Terminalia catappa L is one of the plants classified as a pioneer species and can grow on the poor nutrient land and easy to cultivation. Research on the additions of cow dung as ameliorant and NPK fertilizer to improve the physical, chemical, and biological of tailings media in nursery to the growth of Terminalia catappa L. Treatment was given to the growth of seedlings of Terminalia catappa L using the Completely Randomized Design (RAL) with 2 (two) factor treatment. The first factor is NPK Fertilizer with 5 level treatment such as without Fertilizer (K0), 5 gr (K1), 10 gr (K2), 15 gr (K3), 20 gr (K4). The second factor is an organic compound from cow dung with 5 level treatment such us without cow dung (P0), 10 gr (P1), 20 gr (P2), 30 gr (P3), 40 gr (P4). Each level of treatment consisting of 3 replications so the amount of seedlings in this research is 75 seedlings. Data collected were short high (cm), stem diameter (mm), number of leaves and dry weight of the plant. The result of addition organic and NPK fertilizer on tailing media in nursery gave a significant effect on the growth of height, diameter, number of leaves and dry weight of Terminalia catappa L. The best result media treatment for all parameters is NPK fertilizer and cow dung with combination 20: 40 gr,Â although almost all of the ameliorant treatment gave the better result if compare the control treatment without addition organic ameliorant.Keywords: ameliorant, organic and NPK Fertilizer, Tailings, Terminalia catappa L.